(untitled) (Journal of the College of Basic Education, 2022)
In recent time, through studied and modern scientific research, a great interest emerged in the topic of obesity (overweight), especially for women, as some reasons that obesity is caused by lack of movement and low level of performing kinetic exercises, which in turn led to the weakness of kineticcapabilities and appearance of high proportions of fat and cellulite.Hence, the importance of this research is an attempt to explain the influence of kinetic exercises associated with the diet system on the development of some kinetic capabilities and fat and cellulite ratios for women of 20-30 year age. Research Objectives: The objectives of this research include as follows: 1- Preparing a program for kinetic exercises that fits the capabilities of research sample. 2- Preparing a diet system that suits the nature of research sample. 3-Knowledge of kinetic capabilities and proportions of fat and cellulite for the research sample. 4- Knowledge of the effect of kinetic exercises and diet system on some kinetic capabilities and ratios of fat and cellulite for the research sample. Research Hypothesis: There statistical differences between prior and posttests which are in favor of these tests in some kinetic capabilities and proportions of fat and cellulite for women of 20-30 year age. Areas of Research: 1) The humen field: A sample of (22) women of 20-30 year age. 2) The temporal field: For the period from 21-5-2016 to 29-9-2016. 3) Spatial field: Fitness gallery at the University of Technology. Methodology of Research and Field Procedures 1)The researcher used the experimental method in one of the main designs, namely prior- and post-tests per one experimental set, while the research sample was 22 females who ad registered in the fitness gallery at the university. 2) The researcher, through performing the reconnaissance, showed how to conduct the prior physical measurements which included the fat ratios for some regions of the body and weight index. Then, the researcher explained how to do the steps of field procedures for the research sample and demonstrated the post measurements and the statistical means used in research. 3)After the implementation of the kinetic exercises, diet system and conducting the post tests, the researcher presented the results and discussed them according to the findings reached. The results were discussed by a scientific method depending on sources and references relevant to the research topic as well as relying on the researcher’s observances and remarks during the implementation of the training course and measurements. Conclusions: 1) The use of kinetic exercises and diet system by the women of 20-30 year age helped to increase some of the kinetic capabilities and reduce the proportions of fat and cellulite. 2) The kinetic exercises and diet system for women of 20-30 year age have a positive effect in reducing the fat ratios in some regions of the body under research, and accumulations of fat, water and waste in the regions (shoulder, upper arm, hip and thigh), known as cellulite, since the vales were significant. 3) The diet system which was accurately prepared with all available elements made its application easy for the research sample, and every one can follow it. Recommendations: 1) It is necessary to rely on the use of kinetic exercises and diet system to develop the kinetic capabilities and reduce the proportion of fat and the accumulation of waste and water and fats in buttocks which is called cellulite. 2) It is necessary to know the kinetic capabilities, the physical indices and cellulite ratios due to their importance in the health side. 3) It is necessary to follow the modern scientific methods in training, and the continuous tracking for the trainees by the health centers and physical fitness centers. 4) The health awareness through the audio-visual media to educate and guide the citizens for healthy food habits and the importance of sport practice for the sake of health.